Emergência de classes seqüenciais após treino com pareamento consistente - RIBEIRO, Mylena Pinto Lima (2013)
Order relations can be documented by behavioral tests that evaluate whether such relations posses the properties of asymmetry, transitivity and connectedness. We used matching to sample with prerequisites for the emergence of sequential class. In the present study, we assess whether sequential classes were also produced after a trial with consistent matching, without immediate differential consequences. Five undergraduate students of both sexes were submitted to the training of conditional relations AB, AC and AD. The participants task were to choose abstract geometric figure from digits. After teaching the conditional relations, the participants were exposed to tests of ordering the stimuli in three sequences with five different stimuli, tests for ordering pairs of the stimuli that occupied adjacent and not adjacent positions in the sequence of five stimuli, and tests of multiple substitutions of stimuli, without additional training. Three participants reached the learning criterion in the training of the conditional relations and obtained high number of successes in the sequential tests. The consistency training without immediate differential consequences was effective to establish order relations among stimuli, without explicit training with normal adult participants. These results replicate data reported the literature on the establishment of sequential performance after matching to sample training.